Spray-Dried Microencapsulation of Oregano (Lippia graveolens) Polyphenols with Maltodextrin Enhances Their Stability during In Vitro Digestion - Manuel de Jesús Bernal-Millán; Erick Paul Gutiérrez-Grijalva; Laura Contreras-Angulo; M. Dolores Muy-Rangel; L. Xochitl López-Martínez; J. Basilio Heredia (Journal of Chemistry)
The effect of in vitro gastrointestinal digestion on the release of microencapsulated phenolic compounds was evaluated through an optimized spray drying process. A stock extract of oregano phenolic compounds was developed and microencapsulated in a spray dryer following a central composite rotatable design, controlling the variables, inlet temperature (111.7-168.2°C), and percentage of wall material (5.8-34.1%). Optimum drying conditions for spray drying were decided based on different yield percentages (Y %) and encapsulated phenolic compounds (EPC). The analyzed physical properties were morphology measured by electron microscopy and humidity; other properties evaluated were the content of total phenolic compounds, antioxidant capacity determined by DPPH and ABTS assays, and phenolic profile by ultraperformance liquid chromatography coupled to mass spectrometry (UPLC-MS). During the gastrointestinal simulation, a stability of 85% was determined in the intestinal stage. Microencapsulation technology by spray drying is an excellent selection to stabilize and protect bioactive compounds of oregano and promote its use as a functional ingredient.